Music in the Horror Films of Val Lewton - Lee, Michael (Edinburgh University Press, 2022)
Examines how the music in Val Lewton's horror films enhanced the films' aesthetics and visual styleProvides a fine-grained analysis of each film's original scoreExplores all examples of source music in each filmConsiders film music as a path to film analysisVal Lewton's horror films revolutionized a popular genre through a much-studied and still widely emulated visual style emphasizing shadows and absences. By denying audiences visual confirmation of horror, his reforms placed a fresh burden on the soundtrack of his films. This book offers a fine-grained study of the Lewton unit's transformational sonic style which introduced the first jump scare," liberal use of pre-musique concrète, and an original orchestral score for every film in the series in violation of "B" movie norms. Their orchestral scores often exceed the conventions of film music as we hear the RKO Music Department ignoring instructions thus freeing their contributions to signpost the path toward each films' essential themes.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2022)
Keywords: Lewton, Val -- 1904-1951; Geschichte; Film, Media & Cultural Studies; PERFORMING ARTS / Film & Video / Direction & Production; Horror films -- History and criticism; Motion picture music -- History and criticism; Filmmusik; Horrorfilm